THE CHARACTERIZATION OF BYRONIC HERO IN THE MAIN CHARACTER OF THE NOVEL LOKI: WHERE MISCHIEF LIES BY MACKENZI LEE: A MICHAEL RIFFATERRES SEMIOTIC ANALYISIS - Amalia Putri, Meitha Charissa; Widisanti, Ni Made; Ratih P, Shita Dewi (Universitas Pakuan, 2022)
Byronic hero is a type of Romantic Hero that was popular in the Romantic period in the 19th century. The purpose of this research is to identify Loki as a Byronic Hero in Loki: Where Mischief Lies by Mackenzi Lee. This research uses qualitative analysis methods with a structuralism approach, which focused on intrinsic elements of the novel such as character and characterization, conflicts, and symbols. By applying Michael Riffaterres theory of semiotics, this research describes the character traits of Byronic Hero through heuristic and hermeneutic readings on Lokis character describes the meaning of the symbols